Mind the Gap: Workshop Satisfaction and Skills Development in Art-Based Learning (European Journal of Teaching and Education, 2022)
Research on art-based leadership development suggests that this form of multimodal experiential learning enhances soft skills. Against this backdrop, two quantitative sub-studies from a research program on leadership development explored training effects of improvisational theater and visual arts. In both sub-studies, we applied a longitudinal pretest-posttest design and compared skills development with learner satisfaction and perceived usefulness of educational content. Our findings suggest that participants overestimate training success because very high satisfaction and favorable opinions on the programs’ practical relevance are not reflected in desired skills development. We interpret this discrepancy as a halo effect, in which the fun factor of art-based learning and other facets of aesthetic experience outshines actual learning results. Despite limitations such as small sample sizes, our findings contribute to research by putting overly positive assumptions on art-based learning’s effectiveness into perspective.